PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP TINGKAT STRES WARGA BINAAN WANITA (KASUS NON NARKOBA) DI LAPAS ANAK PEKANBARU - Waldani, Janulusia; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : this study aimed to determine the effect of group guidance service on stress levels the female inmates (non drug cases) at pekanbaru children’s correctional institution. The research method used in this research pre experimental method using The One Group Pre-test Post-test Design. The research wa done twice before the experiment (pre test) and after experiment (post test) with one group of subject. Data analysis used in this research is descriptive qualitative and quantitative analytic. Subjects in this study were selected using non-probability sampling technique with purposive sampling method amounting to 7 non-drug users of non-drug cases. This research was conducted by providing group guidance service for 5 meetings. The analysis was used Wilcoxon test. The result showed significant influence of group guidance service to stress levels (Asymp. Sign obtained at 0,043 where 0,043 < 0,05 = signicficant).Keyword : Stress, Group Guidance, Women Inmates